The analysis of the milk production and the body condition on two Saanen goat-farms - Kocsisné Gráff, Myrtill; Jávor, András; Kukovics, Sándor (Acta Agraria Debreceniensis, 2009)
The authors carried out an examination on two Saanen goat farms during four months from May to August 2008. The body condition score and milk production of the goats were measured. In data processing analysis of variance was used to compare the data of the studied farms. They tried to find the answer for the question how the body condition scores and milk production change in each month. The changes observed in each farm were examined separately then they compared the values of the two farms.. On one of the farms the nutrition was proper therefore with an ideal, intermediate body condition (average 2.73) the goats produced a good amount of milk (2.5 milk-kg/mother/day). On the other farm the nutrition was not proper, therefore the body condition of the goats was weak (average 1.88). Their milk production decreased significantly from month to month (average 2.35 milk-kg/mother/day). The authors could conclude considering both farms that the more milk the goats produced, the lower their body condition score became. The two parameters showed negative correlation.